Boganmeldelser - Peter Garde; Vagn Greve; Petter Asp; Hans Klette; Hans-Jørgen Wallin Weike; Henrik Zahle; Birgitte Vestberg; Joi Bay; Beth Grothe Nielsen (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews